Sharia Entrepreneurship based on Tourism: a Study of Coastal Area Economic Development in Tanjung Sampang Village - Sugianto Sugianto; Safira Adibatul Faruq; Rudy Haryanto; Fadllan Fadllan; Basar Dikuraisyin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The Sea Pick tradition in Tanjung Village, Sampang, is an annual ritual steeped in social, religious, and cultural values. Over time, this tradition has undergone changes, incorporating entertainment elements such as musical performances, decorated boat races, and food bazaars, while maintaining its sacred values ”‹”‹and core rituals. These changes aim to attract tourists while also increasing public understanding of the importance of preserving traditions. The impact of this transformation is evident economically, with coastal communities gaining new business opportunities through fish sales, culinary specialties, and transportation services, thus contributing to the tradition's role in supporting a sustainable local economy. Socially and culturally, Sea Pick strengthens community identity, fosters solidarity among residents, and fosters cultural education for the younger generation. However, some traditional leaders are concerned about the erosion of sacred values ”‹”‹due to the dominance of entertainment. This study emphasizes that Sea Pick can serve as a model for integrating cultural preservation, economic development, and social education in coastal communities..